Analisis Kepuasan Pengguna Website Repository Universitas Amikom Purwokerto menggunakan Metode System Usability Scale (SUS) - Nur Adiya, Az Zahra Dwi; Anindya Fidela; Dea Lili Anggraeni; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This study aims to analyze user satisfaction with the Universitas Amikom Purwokerto repository website using the System Usability Scale (SUS) method. In the digital era, online repositories play a crucial role as a platform for storing, managing, and distributing academic work, supporting academic activities and knowledge exchange. However, observations indicate that the repository website faces challenges in accessibility, including unintuitive navigation, difficult-to-understand menus, and limited language options, as it is only available in English. Through a SUS survey involving 100 respondents, an average SUS score of 46 was obtained, falling into the "Not Acceptable" category with a grade of "F" and an adjective rating of "Poor." This result indicates that the website’s usability is insufficient and requires improvement. Recommendations include enhancing navigation, ensuring interface consistency, providing a dual-language option (Indonesian and English), improving website speed, and conducting regular user satisfaction evaluations. These improvements aim to optimize the Universitas Amikom Purwokerto repository website, thereby providing a better user experience and effectively supporting academic activities and the dissemination of academic work.